A Companion to the Byzantine Culture of War, Ca. 300-1204 - Stouraitis, Yannis (Brill's Companions to the Byzantine World Ser, 2018)
Intro -- Contents -- List of Illustrations -- Notes on Contributors -- Introduction -- Military Power in the Christian Roman Empire, c. 300-1204 -- Yannis Stouraitis -- Part 1 -- The Mentality of War -- Chapter 1 -- The Imperial Theology of Victory -- Paul Stephenson -- Chapter 2 -- State War Ethic and Popular Views on Warfare -- Yannis Stouraitis -- Chapter 3 -- Civil War in the Christian Empire -- Yannis Stouraitis -- Chapter 4 -- The Enemies of the Empire: Portrayed Images -- Michael Grünbart -- Chapter 5 -- Warfare as Literary Narrative -- Stamatina McGrath -- Chapter 6 -- Alternative Means of Conflict Resolution -- Tilemachos Lounghis -- Part 2 -- Warfare as Socio-Political Praxis -- Chapter 7 -- Army Structure: Roman Continuity and Byzantine Change -- Savvas Kyriakidis -- Chapter 8 -- Byzantine Fronts and Strategies 300-1204 -- Denis Sullivan -- Chapter 9 -- Naval Warfare: Military, Institutional and Economic Aspects -- Salvatore Cosentino -- Chapter 10 -- Siege Warfare: The Art of Re-capture -- Christos G. Makrypoulias -- Chapter 11 -- The Army in Peace Time: The Social Status and Function of Soldiers -- Philip Rance -- Chapter 12 -- Military Technology: Production and Use of Weapons -- Georgios Theotokis -- General Bibliography -- Index.